2011
DOI: 10.1148/rg.314105160
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted Imaging of the Breast: Principles and Clinical Applications

Abstract: Diffusion-weighted imaging provides a novel contrast mechanism in magnetic resonance (MR) imaging and has a high sensitivity in the detection of changes in the local biologic environment. A significant advantage of diffusion-weighted MR imaging over conventional contrast material-enhanced MR imaging is its high sensitivity to change in the microscopic cellular environment without the need for intravenous contrast material injection. Approaches to the assessment of diffusion-weighted breast imaging findings inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
162
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(176 citation statements)
references
References 76 publications
(116 reference statements)
9
162
1
4
Order By: Relevance
“…Echoplanar DWI, the most common image acquisition scheme used for DWI, can result in image distortion due to eddy currents. Geometric distortion, signal loss, and image-blurring artifacts in EPI are caused by magnetic field inhomogeneities (6,7,12). These artifacts could impair ADC measurements (4,6,17).…”
Section: Discussionmentioning
confidence: 99%
“…Echoplanar DWI, the most common image acquisition scheme used for DWI, can result in image distortion due to eddy currents. Geometric distortion, signal loss, and image-blurring artifacts in EPI are caused by magnetic field inhomogeneities (6,7,12). These artifacts could impair ADC measurements (4,6,17).…”
Section: Discussionmentioning
confidence: 99%
“…The ADC value can be calculated by assessing the signal attenuation that occurs in DWI performed at different b values. Usually, low ADC values indicate restricted diffusion (high cellular density), while high ADC values indicate more free diffusion (low tissue cellularity) (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…It has primarily been used clinically for brain disorders, particularly for the early detection of ischemic stroke or infarction (33)(34)(35)(36). Numerous studies have put forward DWI as a new and valuable cancer imaging biomarker for detection, diagnosis, staging, detecting metastasis or relapse, and assessing treatment response (30)(31)(32)(37)(38)(39)(40)(41)(42)(43)(44). Studies have also demonstrated that, for malignancy imaging, the quantitative analysis of ADC and the standard uptake value (SUV) in fluorodeoxyglucose positron emission tomography (FDG PET)/CT are inversely correlated (37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…DWI measures the random movement of water molecules in tissues, which is detected as the attenuation of the measured signal intensity [11] on Diffusion weighted MRI (DWI). Diffusion can be quantified by using the apparent diffusion coefficient (ADC) value to increase the specificity of DWI [12]. The movement of water molecules is much more restricted in tissues with a higher cellular content and associated with numerous intact cell membranes [13] [14] as seen in malignant breast lesion.…”
Section: Introductionmentioning
confidence: 99%